Pengaruh Human Resource Management dan Leadership terhadap Kinerja Bisnis Bank Syariah (Unit Usaha Syariah) - Amin, Muhammad (Eqien - Jurnal Ekonomi dan Bisnis, 2024)
The research aims to find out how the dependent variables human resources management and leadership relate to the performance of sharia banks (sharia business units). The research method uses a census by sending 20 questionnaires to Islamic banks (Sharia business units) which were carried out in the period July to September 2021. The results of data collection were processed using SPSS version 22 statistics. The research results showed that the dependent variables were human resources management and leadership partially and jointly influences the dependent variable of sharia bank business performance (sharia business unit) which is 82.7%. The implication of the research is that the concept of sharia finance is not only to maximize welfare and consumption through achieving sharia bank business performance but also to maintain a balance between material and spiritual satisfaction (maqashid sharia).